Electing the president, 2004 : the insiders' view - Jamieson, Kathleen Hall (EBL-Schweitzer, 2006)
In this volume, the consultants who brought the country the Bush-Cheney and Kerry-Edwards presidential campaigns of 2004 explain the strategies behind the ads and debates, discuss what they did and failed to do to elect their candidates, and reveal their differing perspectives on the issues that mattered.